Synthesis of hollow hydroxyapatite for biomedical applications. - Moo, Ying Xin. (2009)
Hollow porous hydroxyapatite nanoparticles have been successfully synthesized using calcium carbonate as sacrificial template. Calcium carbonate template was prepared by reacting Ca(NO3)2.4H2O and Na2CO3 solution with the addition of Poly sodium4-styrene-sulfonate (PSS) as surface modifier at room temperature. Under hydrothermal treatment, PO43- anions undergo ion exchange with CO32- anions, forming pores at the surface of the particles. The template core is not being removed by using dilute acid to dissolve the core template, but instead it undergoes ion exchange and Kirkendall effect and as a result vacancy and pores formed. The size and morphology of HA formed follows the size and morphology of the calcium carbonate template. Different sizes and morphologies such as spherical and cubic HA particles were synthesized. Various parameters such as aging time, temperature, pH values and templates with different morphologies and size were adjusted to investigate the effect on synthesizing the hollow HA nanoparticles. The drug loading and release effect was done and ibuprofen was loaded into hollow hydroxyapatite particles to be investigated. The overall drug release percentage reached around 60%.